Parental communication patterns and psychological well-being among in-school adolescents - Augustine Idowu Omoruan; Janet Fumilayo Omoruan; Shuaib Abolakale Muhammed; Afeez Folorunsho Lawal (Academic Journal of Psychology and Counseling, 2026)
Parent–adolescent communication plays a vital role in adolescents’ psychological well-being, yet evidence on specific communication patterns in Nigeria remains limited. This study examined the prevalence of parental communication styles and their influence on the psychological well-being of in-school adolescents, anchored by the Family Communication Patterns Theory. A sample of 200 senior secondary school students was randomly selected. Data were collected with an adapted Parental Communication Patterns Questionnaire (PCPQ) and a psychological well-being scale. Descriptive statistics, t-tests, one-way ANOVA, and multiple regression were used for analysis. Findings showed that consensual (M = 17.07, SD = 2.43) and protective (M = 17.30, SD = 2.98) communication were the most common. Regression results indicated that consensual (β = 0.263, p = 0.011) and laissez-faire (β = 0.628, p < .001) significantly predicted psychological well-being. Pluralistic and protective patterns were not significant. The study recommends parent-focused communication workshops in schools and communities.